Adjunctive Plasma Rich in Growth Factors in the Treatment of Osteomyelitis and Large Odontogenic Cysts Prior to Successful Implant Rehabilitation: Case Report - Marc DuVal; Mohammad Hamdan Alkhraisat (MDPI AG, 2023)
Osteomyelitis of the jaws presents a clinical challenge to conventional treatment, often requiring multiple surgical interventions resulting in significant deformity and presenting significant problems to satisfactory rehabilitation. While benign odontogenic cysts, such as the radicular cyst, are generally predictably treated, they can cause significant localized bone destruction and thus can present significant problems in satisfactory rehabilitation. In this case report, patients were treated combining conventionally appropriate surgical debridement and oral antibiotics with adjunctive plasma rich in growth factors (PRGF). Patients showed a complete soft tissue and osseous regeneration to their pre-pathologic state, with successful implant rehabilitation. PRGF appears to be highly successful in minimizing or eliminating osseous deformities normally associated with conventional treatment of osteomyelitis of the jaw and treatment of large odontogenic cysts. Future trials must be performed to confirm these results in comparison to controls using conventional treatment alone.